Effect of fruit on glucose control in diabetes mellitus: a meta-analysis of nineteen randomized controlled trials - Ren, Yu; Sun, Shuang; Su, Yongwei; Ying, Chenfei; Luo, Hua (Frontiers in Endocrinology, 2023)
Objective: Diabetes mellitus is a worldwide health problem, and it remains unclarified whether fruit is beneficial in glycemic control. This study aimed to analyze evidence from randomized controlled trials evaluating the effect of fruit consumption on glucose control. Methods: We searched the PubMed, EMBASE, Ovid, Web of Science, and Cochrane Central Register of Controlled Trials databases from the respective database inception dates to December 30, 2022, to identify randomized controlled trials that evaluated the effects of fruit consumption on glucose control. Two researchers independently screened the studies in accordance with the inclusion and exclusion criteria, and performed the literature quality evaluation and data extraction. RevMan 5.4 software was used to perform the data analysis. Results: Nineteen randomized controlled trials with 888 participants were included. Fruit consumption significantly decreased the fasting blood glucose concentration (MD -8.38, 95% CI -12.34 to -4.43), but showed no difference in the change in the glycosylated hemoglobin (MD -0.17, 95% CI -0.51 to 0.17). Subgroup analyses further suggested that the consumption of both fresh and dried fruit affected the fasting blood glucose concentration. Conclusions: Increasing the fruit intake reduced fasting blood glucose concentration. Therefore, we recommend that patients with diabetes eat more fruits while ensuring that their total energy intake remains unchanged.